2017
DOI: 10.1193/082916eqs138m
|View full text |Cite
|
Sign up to set email alerts
|

Framework for a Ground-Motion Model for Induced Seismic Hazard and Risk Analysis in the Groningen Gas Field, The Netherlands

Abstract: The potential for building damage and personal injury due to induced earthquakes in the Groningen gas field is being modeled in order to inform risk management decisions. To facilitate the quantitative estimation of the induced seismic hazard and risk, a ground motion prediction model has been developed for response spectral accelerations and duration due to these earthquakes that originate within the reservoir at 3 km depth. The model is consistent with the motions recorded from small-magnitude events and cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 29 publications
3
106
0
Order By: Relevance
“…Another study using a different hazard model also found an elevated seismic hazard for the region . Similar trends have been observed elsewhere for induced seismicity associated with hydraulic fracturing and gas production . By convolving the hazard model from Petersen et al with assumed fragility models for collapse and the threat to life safety from falling hazards, Liu et al found that this increased seismic hazard also elevated these risks substantially compared with the baseline natural seismicity.…”
Section: Literature Reviewsupporting
confidence: 58%
“…Another study using a different hazard model also found an elevated seismic hazard for the region . Similar trends have been observed elsewhere for induced seismicity associated with hydraulic fracturing and gas production . By convolving the hazard model from Petersen et al with assumed fragility models for collapse and the threat to life safety from falling hazards, Liu et al found that this increased seismic hazard also elevated these risks substantially compared with the baseline natural seismicity.…”
Section: Literature Reviewsupporting
confidence: 58%
“…Site profiles were used with permission from NAM. Details on these profiles were published in Kruiver et al (2017) …”
Section: Data and Resourcesmentioning
confidence: 99%
“…The sites are underlain by bedrock with a shear velocity of 1,400 m/s. These sites are real sites within the Groningen gas field in the northwestern Netherlands where shear wave velocity measurements were conducted in the upper 30 m, and shear wave velocities of the deeper layers were estimated using geophysical methods and deep borehole measurements (Kruiver et al, 2017).…”
Section: Amplification Functionsmentioning
confidence: 99%
“…The focus of this paper is to propose a transparent procedure to separately calculate and incorporate the contribution of uncertainty in the MRD curves to the total uncertainty in the AFs for a site. To illustrate the procedure, we present its application to the site response model for the Groningen gas field in the Netherlands where hydrocarbon production is leading to induced earthquakes, in response to which a comprehensive seismic hazard and risk assessment is being undertaken (Bommer et al [4]). A component of the hazard model is a site response model for the entire Groningen field (Rodriguez-Marek et al [5]).…”
Section: Introductionmentioning
confidence: 99%